Water systems' revitalization: interventions adopted in aquatic ecosystems in Brazil and worldwide - Oliveira, Alinne Gurjão de; Crispim, Maria Cristina (Gaia Scientia, 2018)
Water bodies are key elements for the subsistence and maintenance of civilizations. However, the growing populations and theoften-adopted management models of the water resources have exerted a strong impact on these, making them unsuitable for a range of uses.In order to improve the water quality and the nearby environmental conditions, several revitalization actions of watercourses have been implemented.This work presents options of actions that can be executed and the outcome of revitalization operations that took place in watercourses in Brazil and around the world. It also presents proposals for improving aquatic systems in João Pessoa city, Paraíba, Brazil.